Improving the Quality of Crackers by Integrating the Taguchi Method and Failure Modes and Effects Analyze (Fmea) in Cv. Nobility - Anda Bagus Setiawan; Wiwik Sulistyowati (Procedia of Engineering and Life Science, 2021)
CV Budi Luhur is a company that produces onion crackers as their main product. In addition, CV Budi Luhur also produces shrimp juice crackers. The company located in Tulangan Sidoarjo is not missed also with the name of failure. For example, in onion cracker products there are problems with taste and crispness so that there is a decrease in sales. Data processing begins by disseminating questionnaires to consumers, then identifying problems using FMEA methods and conducting interviews with companies so as to provide alternatives to determine the best composition for experiments and take the best level at each pre experiment aimed at consumers to be processed in the minitab19 application and draft proposals to compare consumer interest in old compositions and new compositions.From the results of data processing by using Taguchi in the results of the mean 2 population test conducted showed an increase in taste response and humility response where the taste response got interest by 53% from the initial 18% and the humility response got an interest of 58% from the initial 23%. This shows the similarity of the draft proposal is preferred by consumers in terms of taste and humility.